Small beam dosimetry: A multi-center multi-detector italian project. (September 2016) - Talamonti, C.; Russo, S.; Barone, Tonghi L.; Benecchi, G.; Borzi, G.; Bresciani, S.; Cagni, E; Carbonino, C.; Casale, M.; Clemente, S.; Consorti, R.; D'Alessio, V.; et al.
Abstract : A project dedicated to stereotactic body radiotherapy (SBRT) dosimetric aspects started in the framework of the Italian Association of Medical Physics (AIFM) SBRT working group. Its main objectives are manifold but sharing the knowledge between different clinics is the one of the most important. More than 30 centres, equipped with Varian, Elekta, Siemens or CyberKnife linac were enrolled. The project was divided in several work-packages, the first one evaluated the relative measurements with detectors routinely used by individual centers and in the following different detectors run in various centre. Each centre in the same work-package performed dose profile of field size ranging from 0.6 × 0.6 cm 2 to 5.0 × 5.0 cm 2, and relative output factors (ROF) measurements with a diamond or silicon diode or scintillator detector. In workpackage-1 ROF values measured in the first phase were compared with the ones measured with a microdiamond showing a higher inter-center consistency with this dosimeter compared to routine detectors. In workpackage-2 a silicon diode of new generation was used also to develop a mathematical relation from multicentric experimental data, which describes and predicts the ROF as a function of effective field size for TrueBeam Varian and Elekta linacs. Workpackage-3 used a plastic scintillator for TPR20, 10 and ROF; the latter showed a greater variability. Workpackage-4 used diamond and plastic scintillator with Cyberknife beams, to evaluate if microDiamond could be a suitable alternative to silicon diodes for OF determination and to validate the feasibility of using the scintillator as a reference detector in consideration of the ČerenkovLightRatio and experimental uncertainties. The results of the study for all the detectors emphasized the usefulness of a multi-center validation over a single center approach.